Advanced geometry modelling of 3D woven reinforcements in polymer composites: processing and performance analysis - Zeng, Xuesen; Brown, Louise P.; Endruweit, Andreas; Long, Andrew C. (2012)
Numerical methods have become increasingly effective tools for analysis and design of composite materials. This study investigates how the inclusion of geometrical variations in modelling 3D woven fabrics affects the accuracy of numerical predictions. Based on micro-Computed Tomography data of 3D orthogonal woven composites, unit cell models were generated in TexGen at different levels of geometrical detail. Two types of analysis were implemented: (a) computational fluid dynamics (CFD) simulates resin flow during fabric impregnation in composites processing to predict permeability; (b) implicit static finite element analysis predicts in-plane tensile strength of the composites. By comparison with experimental data, the numerical predictions indicate that local geometrical variations, particularly in yarn cross-section, surface crimp and binder yarn path, have significant influence on both permeability and material strength. It is important to model the precise geometry in certain locations while the overall geometry can be simplified in order to maintain the practicality of model generation.